РОЗРОБКА ТА ДОСЛІДЖЕННЯ АЛГОРИТМІВ ВИМІРЮВАННЯ ПАРАМЕТРІВ ЕЛЕКТРОЕНЕРГІЇ У РАЗІ ВИКОРИСТАННЯ ФІКСОВАНОЇ ЧАСТОТИ ДИСКРЕТИЗАЦІЇ СИГНАЛІВ - Карасінський, О.Л.; Тесик, Ю.Ф. (Інститут електродинаміки НАН України, Київ, 2024)
A study of the possibilities of measuring current values, phase shift angles and other parameters of electrical networks using these data, when sampling with a frequency not multiple of the network frequency, was carried out. In the proposed algorithm, an intermediate linear approximation is used to calculate the instantaneous values of interpolated signals at equidistant moments of time during the period of the main frequency of the network. The cases when such sampling is performed on one device with sequential or simultaneous coding of input signals and the case when sampling frequencies do not match in each measurement channel are considered. A study of the use of these methods was conducted using the developed computer model and layout of the distributed measurement system. References 32, figures 19.